A concept analysis: Support for lay healthcare workers in HIV services, Bojanala District, North West - Sarah B. Pitse; Patrone R. Risenga (Curationis, 2023)
Background: Different lay healthcare workers play an important role in the retention of clients to human immunodeficiency virus (HIV) care. Retention to HIV care is crucial to promote treatment continuation, viral suppression and reduced risk of transmission. However, lay healthcare workers view and perceive support differently.